Analysis of Traffic Safety Levels in Tanah Laut Regency - , Hafsha Yanti Siregar (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Traffic accidents are a serious problem that affects the safety of road users, economic losses, and the quality of life in society. Tanah Laut Regency, as one of the areas experiencing rapid mobility growth, faces various challenges in maintaining traffic safety levels. The objective of this study is to evaluate the level of traffic safety on the highways in Tanah Laut Regency, represented by accident rates based on population size, road length, and severity indices. The calculation method follows the approach developed by Pignataro (1973), using data on the number of accidents and casualties recorded in Tanah Laut Regency. The results show that the accident rate per population will increase from 11.176 in 2020 to 26.640 in 2023, and then decrease to 25.903 in 2024. In terms of road length, the rate increased from 0.019 in 2020 to 0.047 in 2023, then decreased slightly to 0.046 in 2024. However, the severity index shows a decrease from 0.872 in 2020 to 0.696 in 2022, followed by an increase to 0.759 in 2023 and then a slight decrease to 0.717 in 2024. This indicates a decline in the road safety level in Tanah Laut Regency, and highlights the need for serious efforts by the Tanah Laut Regency Government, involving all relevant stakeholders, to address this issue.